FIRST REPORT OF NEW WILT DISEASE ON Mangifera indica CAUSED BY Ceratocystis fimbriata IN INDONESIA - Rahmat Pratama; Ahmad Muslim; Suwandi Suwandi (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2023)
Ceratocystis wilt and canker disease has severely compromised the profitability of Mangifera indica plantations in the world. In 2022, wilt and sudden death were observed on Mangifera indica. Identification was performed by sequence analysis of the concatenated β-tubulin gene regions. Sequencing of the PCR product confirmed this pathogen was Ceratocystis fimbriata sensu stricto. This is the first report of C. fimbriata causing sudden death disease in M. indica in Indonesia.